PC-PNDT act: perspectives of medical undergraduates in a Sub-Himalayan state - Gupta, Rajiv Kumar; Singh, Parveen; Hussain, Shahid; Kumari, Rashmi; Langer, Bhavna; Gupta, Riya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Sex selective abortions have grossly distorted the child sex ratio in India. Role of medical technology in declining sex ratio at birth cannot be undermined. To combat this social evil, PC-PNDT (Pre-conception Prenatal Diagnostic Test) was promulgated in 2003 by Government of India. Enhancing the knowledge of medical fraternity with focus on undergraduate students can imbibe an enduring commitment towards this predicament Methods: The present cross-sectional study was conducted in Government Medical College of Jammu. Students of 1st year MBBS of Batch 2016-2017 were administered the pre-designed and pretested questionnaire. Information was collected regarding sex determination as well as PC-PNDT Act. Results: 80% respondents knew about the declining sex ratio and 95% knew that sex determination is possible during pregnancy. Only 24.29% had heard about PC-PNDT Act although 95% knew that prenatal sex determination is punishable. Higher proportions of female respondents were aware of both fine and imprisonment as punishment under the act. (p<0.05). Regarding technique used for sex determination, males had better knowledge about ultrasonography than their female counterparts (p<0.05). More females would like to have male child as preferred first child (p<0.05) and 87.14% of respondents preferred that sex determination be punished more vigorously. Conclusions: Awareness about some of the parameters about PC-PNDT Act among the medical undergraduates was poor and it would be pertinent to hold more educational sessions for them.